2019
DOI: 10.1016/j.jnucmat.2018.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of hardening contribution of G-Phase precipitation and spinodal decomposition in aged duplex stainless steel: APT analysis and micro-hardness measurements

Abstract: h i g h l i g h t s Link of microstructural characterization to microhardness of the ferrite for a wide variety of duplex steels. Quantification of G-phase and spinodal contributions to ferrite hardening. G-phase can be the main contributor to hardening.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(19 citation statements)
references
References 37 publications
1
15
0
Order By: Relevance
“…In some research works the effect of G-phase on mechanical properties is reported as negligible compared to the one of Fe-Cr unmixing, considered as the main responsible for properties change [5,28,33] and in others, it is claimed that G-phase had an important role in the material hardening [34,35]. Although, a very recent work by Badyka et al seems to prove that in many cases G-phase may play an important role in the material hardening during aging [12]. But the respective part of each mechanism in the properties evolution depends on the material under study and the aging conditions.…”
Section: Heterogeneous and Homogeneous G Phase Precipitationmentioning
confidence: 99%
See 2 more Smart Citations
“…In some research works the effect of G-phase on mechanical properties is reported as negligible compared to the one of Fe-Cr unmixing, considered as the main responsible for properties change [5,28,33] and in others, it is claimed that G-phase had an important role in the material hardening [34,35]. Although, a very recent work by Badyka et al seems to prove that in many cases G-phase may play an important role in the material hardening during aging [12]. But the respective part of each mechanism in the properties evolution depends on the material under study and the aging conditions.…”
Section: Heterogeneous and Homogeneous G Phase Precipitationmentioning
confidence: 99%
“…This change in mechanical properties of the material is caused by evolutions of its complex initial microstructure, which we have presented in details in a former work [7]. The two main microstructural changes during such stainless steels' aging are the precipitation of a Ni, Mn and Si-rich phase and the Fe-Cr matrix unmixing, both at the nanometer scale [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to its very large impact on the industrial use of stainless steels, this Fe-Cr decomposition has been extensively studied over the past decades. Experimental characterization of the degree of unmixing has been mainly carried out using Atom Probe Tomography (APT) [2,4,[6][7][8][9][10][11][12][13][14][15] and Small-Angle Scattering (using neutrons or X-rays, respectively SANS and SAXS) [16][17][18][19][20][21][22][23][24][25]. These experimental data have extensively served as a basis for establishing the validity of physically-based models, most often using Kinetic Monte Carlo modelling, and for establishing the link between the degree of unmixing and the evolution of mechanical properties [2,4,9,15,24,[26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…Cast duplex stainless steel (CDSS) is widely used in the primary coolant pipe of a pressurized water reactor (PWR) nuclear power plant because of its excellent comprehensive properties [ 1 , 2 , 3 , 4 , 5 ]. However, CDSS is prone to phase decomposition when it is in the range of 280–500 °C for a long time, resulting in thermal aging brittleness, which reduces the plasticity and toughness of the material and increases the hardness and brittleness, thereby increasing the possibility of a sudden failure of components and affecting the safe operation of nuclear power plants [ 6 , 7 , 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%